Changes to southern Appalachian water yield and stormflow after loss of a foundation species. Issue 3 (5th August 2014) - Brantley, Steven T.; Miniat, Chelcy Ford; Elliott, Katherine J.; Laseter, Stephanie H.; Vose, James M.
Abstract: Few studies have examined how insect outbreaks affect landscape‐level hydrologic processes. We report the hydrologic effects of the invasive, exotic hemlock woolly adelgid (HWA) in a headwater catchment in the southern Appalachian Mountains. The study watershed experienced complete mortality of an evergreen tree species, Tsuga canadensis (L.) Carr. (eastern hemlock), after infestation was first detected in 2003. Hemlock mortality resulted in a ~6% reduction in basal area in the watershed, and this loss was primarily concentrated in riparian zones. We used a paired‐watershed approach to quantify changes in water yield and peak stormflow using streamflow data from the infested watershed and a nearby watershed with significantly lower hemlock basal area. We hypothesized that yield would increase shortly after hemlock infestation but decrease over the longer‐term. We found that annual yield did not increase significantly in any year after infestation but decreased significantly by 12·0 cm (~8%) in 2010. Monthly yield also decreased after infestation, but changes were limited to the dormant season. The decline in yield is likely to persist as hemlock is replaced by species with higher transpiration rates. Peakflow increased significantly after infestation during the two largest flow events in the post‐infestation period. Changes in stormflow during extreme events may have been temporary as another evergreen, Rhododendron maximum, may have mitigated some of the changes after hemlock loss. Thus, streams draining watersheds where eastern hemlock has been lost due to HWA infestation demonstrate permanent reductions in yield and transient increases in peakflow during large‐flow events. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.